2017
DOI: 10.1289/ehp232
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Causal Effects of Local Air Pollution on Daily Deaths: Effect of Low Levels

Abstract: Background:Although many time-series studies have established associations of daily pollution variations with daily deaths, there are fewer at low concentrations, or focused on locally generated pollution, which is becoming more important as regulations reduce regional transport. Causal modeling approaches are also lacking.Objective:We used causal modeling to estimate the impact of local air pollution on mortality at low concentrations.Methods:Using an instrumental variable approach, we developed an instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 80 publications
1
62
0
2
Order By: Relevance
“…This could be partially attributed to bush fires or controlled burnings, which we were not able to examine in this study. Unfortunately, levels below a regulatory standard are no guarantee of safety, and in fact there is substantial literature documenting the strong connection between adverse population health outcomes and air pollution when analyses are restricted to days when air pollution levels are within regulatory standards 37,38 The significantly higher daily mean levels observed in the Lower and Upper Hunter are reason for concern.…”
Section: Discussionmentioning
confidence: 99%
“…This could be partially attributed to bush fires or controlled burnings, which we were not able to examine in this study. Unfortunately, levels below a regulatory standard are no guarantee of safety, and in fact there is substantial literature documenting the strong connection between adverse population health outcomes and air pollution when analyses are restricted to days when air pollution levels are within regulatory standards 37,38 The significantly higher daily mean levels observed in the Lower and Upper Hunter are reason for concern.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, burning household solid waste emanates many harmful particulates which pollutes the air (Gullett et al, 2010;Hoornweg, D., & Bhada-Tata, 2012;Li, Lei, Bei, & Molina, 2012;Ochoa et al, 2012;Vergara & Tchobanoglous, 2012). Many studies have shown evidence on the deleterious health effects of the pollution emanated from burning solid waste on morbidity and mortality (Burnley, 2014;Kodros, Wiedinmyer, Ford, Cucinotta, & Gan, 2016;Lelieveld, Evans, Fnais, Giannadaki, & Pozzer, 2015;Schwartz, Bind, & Koutrakis, 2017;Shibata, Wilson, Watson, Leduc, & Meng, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…11 Even low levels of air pollutants have been associated with increases in cardiorespiratory diseases. 12 Governments and health organizations have implemented regulations to reduce air pollution levels to protect human health. [13][14][15][16] The WHO assessed air pollution data from more than 3000 cities worldwide and found that half of the cities in high-income countries and one third of those in low-and middle-income countries reduced air pollution levels by more than 5% between 2011 and 2016.…”
mentioning
confidence: 99%